Bimetallic Oxyhydroxide as a High-Performance Water Oxidation Electrocatalyst under Industry-Relevant Conditions. (September 2021) - Yuan, Jiaxin; Cheng, Xiaodi; Lei, Chaojun; Yang, Bin; Li, Zhongjian; Luo, Kun; Koko Lam, K.H.; Lei, Lecheng; Hou, Yang; Ostrikov, Kostya Ken
Abstract: Developing high-performing oxygen evolution reaction (OER) electrocatalysts under high-current operation conditions is critical for future commercial applications of alkaline water electrolysis for clean energy generation. Herein, we prepared a three-dimensional (3D) bimetallic oxyhydroxide hybrid grown on a Ni foam (NiFeOOH/NF) prepared by immersing Ni foam (NF) into Fe(NO3 )3 solution. In this unique 3D structure, the NiFeOOH/NF hybrid was composed of crystalline Ni(OH)2 and amorphous FeOOH evenly grown on the NF surface. As a bimetallic oxyhydroxide electrocatalyst, the NiFeOOH/NF hybrid exhibited excellent catalytic activity, surpassing not only the other reported Ni–Fe based electrocatalysts, but also the commercial Ir/C catalyst. In situ electrochemical Raman spectroscopy demonstrated the active FeOOH and NiOOH phases involved in the OER process. Profiting from the synergy of Fe and Ni catalytic sites, the NiFeOOH/NF hybrid delivered an outstanding OER performance under challenging industrial conditions in a 10.0 mol∙L −1 KOH electrolyte at 80 °C, requiring potentials as small as 1.47 and 1.51 V to achieve the super-high catalytic current densities of 100 and 500 mA∙cm −2, respectively.